2023
DOI: 10.1093/humupd/dmad016
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiological role of estrogens in the initial stages of pregnancy: molecular mechanisms and clinical implications for pregnancy outcome from the periconceptional period to end of the first trimester

Abstract: BACKGROUND Estrogens regulate disparate female physiological processes, thus ensuring reproduction. Altered estrogen levels and signaling have been associated with increased risks of pregnancy failure and complications, including hypertensive disorders and low birthweight babies. However, the role of estrogens in the periconceptional period and early pregnancy is still understudied. OBJECTIVE AND RATIONALE This review aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 227 publications
0
11
0
Order By: Relevance
“…Estrogen, like progesterone, is a key hormone that regulates the development of the uterine lining. During the period when implantation of the embryo occurs, estrogens play a crucial role in preparing the uterus to accept the embryo by activating signaling pathways within the uterine lining [2]. Estrogens need to reach a certain level to start the physical and biological changes that make the uterine lining receptive to embryo implantation [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen, like progesterone, is a key hormone that regulates the development of the uterine lining. During the period when implantation of the embryo occurs, estrogens play a crucial role in preparing the uterus to accept the embryo by activating signaling pathways within the uterine lining [2]. Estrogens need to reach a certain level to start the physical and biological changes that make the uterine lining receptive to embryo implantation [9].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, optimal concentrations of both estrogen and progesterone are necessary for the adequate maturation of the endometrium before embryo implantation [1] (Lessey and Young, 2014). As estrogen operates through paracrine/autocrine signaling rather than direct regulation, it must reach a certain threshold to initiate morphological and biological changes that favor endometrial receptivity for embryo attachment and implantation maintenance [2]. In assisted reproduction cycles, serum estradiol levels reach their peak during follicular maturation.…”
Section: Introductionmentioning
confidence: 99%
“…It would be suggested that the individuals with low E 2 level may have premature menopause, premature ovarian failure, follicle development and other conditions that affect pregnancy. 23 Arzu Yavuz et al showed that lower level of E 2 significantly influenced the clinical pregnancy rate after IUI. 24 Dickey RP et al found that E 2 is associated with birth rate after IUI.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates for the first time that estrogen and progesterone receptors are spatially dysregulated pre-pregnancy and during the peri-implantation maternal–fetal interface of a unique model of superimposed preeclampsia, the BPH/5 mouse. Multiple clinical studies suggest lower concentrations of estrogens in the serum and maternal–fetal interface of preeclamptic women during late gestation, albeit conflicting findings have been reported [ 20 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 54 ]. The role of progesterone in preeclampsia is a subject of even greater controversy, with clinical studies pointing to either increased, similar, or decreased circulating levels in late-gestation preeclamptic pregnancies [ 29 , 30 , 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies to date have only investigated estrogen and progesterone receptor expression in third trimester preeclamptic placentas. Hence, such investigations neglect the dynamic expression pattern of sex hormones and receptors throughout pregnancy, as well as the intricate paracrine signaling between the placenta and adjacent decidua [ 54 ].…”
Section: Discussionmentioning
confidence: 99%